Spherical calcium carbonate particles
By coating the compound with acyl, amino and -COOM groups on the surface of spherical calcium carbonate particles, the problems of insufficient water repellency and excellent curing are solved, and excellent performance suitable for cosmetic applications are achieved.
Patent Information
- Application Number
- CN202380047330.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-21
- Publication Date
- 2025-02-07
AI Technical Summary
The existing spherical calcium carbonate particles are not sufficiently water repellent at high temperatures, and they tend to become too strong when cured, making it difficult to adapt to the application needs of cosmetics and other products.
通过将具有酰基、氨基和-COOM基的化合物被覆在球状碳酸钙颗粒表面,提高其高温下的拒水性,并防止固化时过硬的问题。
It realizes spherical calcium carbonate particles with excellent water repellency at high temperatures and will not become too hard when cured. It is suitable for use in cosmetics and other applications, providing good touch and stability.
Smart Images

Figure BDA0005189509140000151 
Figure BDA0005189509140000191
Abstract
Description
Technical Field
[0001] The present invention relates to spherical calcium carbonate particles, and more particularly to spherical calcium carbonate particles that can be used in cosmetics and the like. Background Art
[0002] In cosmetics, the mixing of spherical particles is widely used to impart ductility, high haze effect, frosted effect, etc. The spherical particles can be roughly divided into particles made of organic polymers such as nylon, polystyrene, and polysilsesquioxane; and particles made of inorganic compounds such as silica and calcium carbonate.
[0003] In recent years, the so-called microplastic problem has become a hot topic. That is, the resin spherical particles mixed in cosmetics flow into the natural world through the sewers, and plankton, fish, etc. ingest the resin particles adsorbed with harmful substances, resulting in the concentration of harmful substances. Therefore, we are currently focusing on the use of inorganic spherical particles that have a large specific gravity and are not easy to float in the ocean, etc., and are actively developing powders and cosmetic formulas. Among them, spherical calcium carbonate, a raw material, has attracted much attention due to its unique soft and smooth touch and lightness.
[0004] Most inorganic compounds are hydrophilic, and powders coated with organic compounds are widely used when inorganic compounds are mixed into cosmetics. That is, surface treatment with organic compounds can give powders lipophilicity, resulting in better touch, high dispersibility in oil, etc. In the past, silicone was often used for surface treatment, but recently, cosmetic users pay more attention to natural materials and prefer surface treatment agents such as fatty acids made from non-petroleum raw materials.
[0005] As a surface treatment technology for spherical calcium carbonate, a technology for treating with fatty acids and silicones has been proposed. For example, Patent Document 1 discloses a method for producing surface-treated spherical calcium carbonate particles for cosmetics, characterized in that an aqueous dispersion of spherical calcium carbonate particles having an average particle size in the range of 0.5 to 20 μm is made to have a pH range of 9 to 11, and in the aqueous dispersion of the spherical calcium carbonate particles, 2.5 parts by weight or more of a higher fatty acid salt relative to 100 parts by weight of the spherical calcium carbonate particles are brought into contact with the spherical calcium carbonate particles at a temperature of 25° C. or more, and then the resulting aqueous dispersion is neutralized to a pH of 6 to 7 at room temperature. In addition, Patent Document 2 discloses a surface-treated spherical calcium carbonate particle for cosmetics, the particle having a hydrous silica coating on the surface of the spherical calcium carbonate particle having a volume median particle size in the range of 0.5 to 20 μm, and also having a silicone oil coating thereon.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-240930
[0009] Patent Document 2: Japanese Patent Application No. 2014-61689 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] As mentioned above, as the surface treatment technology to spherical calcium carbonate, various methods have been developed, but the method for surface treatment with fatty acid disclosed in patent document 1 etc. is not sufficiently water repellent in high temperature water, and there is a problem in stability under high temperature environment, and in addition, due to the use of fatty acid, there is a tendency of strengthening the fixation (aggregation) between powders, therefore, when it is solidified and used for pressed powder, there is a problem of becoming too hard. In addition, the method for silica treatment required for recording in patent document 2 etc. has a long process, and causes the problem of roughness and hard touch from silica when mixed in cosmetics.
[0012] Therefore, a spherical calcium carbonate particle which is excellent in water repellency at high temperature and does not become too hard during solidification is sought.
[0013] The present invention is completed in view of the above-mentioned current situation, and its purpose is to provide a kind of spherical calcium carbonate particles that are excellent in water repellency at high temperature and do not become too hard during solidification.
[0014] Solutions for solving problems
[0015] The present inventor has conducted various studies on the surface treatment of spherical calcium carbonate, and found that the spherical calcium carbonate particles coated with a compound having an acyl group, an amino group and a -COOM group (M represents a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group) have excellent water repellency at high temperatures and do not become too hard during solidification, and it is thought that the above-mentioned problems can be perfectly solved, thereby achieving the present invention.
[0016] The present invention includes the following spherical calcium carbonate particles, etc.
[0017] [1] Spherical calcium carbonate particles coated with a compound (a), wherein the compound (a) has an acyl group, an amino group and a -COOM group (M represents a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group).
[0018] [2] The spherical calcium carbonate particles according to [1] above, wherein the compound (a) is an N-acylamino acid and / or a salt thereof.
[0019] [3] The spherical calcium carbonate particles according to [1] or [2] above, wherein the median particle size (D50) of the spherical calcium carbonate particles measured by a laser diffraction / scattering particle size distribution measuring device is 0.1 to 20 μm.
[0020] [4] The spherical calcium carbonate particles according to any one of [1] to [3] above, wherein the coating amount of the compound (a) is 1 to 10% by weight relative to 100% by weight of the coated spherical calcium carbonate particles.
[0021] [5] A cosmetic comprising the spherical calcium carbonate particles according to any one of [1] to [4] above.
[0022] Effects of the Invention
[0023] The spherical calcium carbonate particles of the present invention include the above-mentioned structure, have excellent water repellency at high temperatures, and do not become too hard during curing, so they can be suitably used in cosmetics and the like. DETAILED DESCRIPTION
[0024] The preferred embodiments of the present invention are described in detail below, but the present invention is not limited to the following description, and can be appropriately changed and applied without changing the gist of the present invention. It should be noted that the combination of 2 or 3 or more preferred embodiments of the present invention described below also belongs to the preferred embodiment of the present invention.
[0025] The spherical calcium carbonate particles of the present invention are coated with a compound (a), which has an acyl group, an amino group and a -COOM group (M represents a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group). The compound (a) in the spherical calcium carbonate particles can be identified by observing the infrared absorption of the acyl group, the amino group and the -COOM group possessed by the compound (a) using an infrared spectrophotometer.
[0026] It is believed that the compound (a) can exert water repellency at high temperatures by utilizing the hydrophobicity derived from the acyl group. It is also believed that since it has an amino group and a -COOM group, it can remove the moisture around the calcium carbonate particles that causes calcium carbonate to aggregate, thereby increasing the fluidity between the particles. Therefore, even when solidified, it does not become too hard, and it is easy to dip it with a puff or sponge and spread it on the skin, giving it a dry touch.
[0027] In addition, the spherical calcium carbonate particles of the present invention are excellent in water repellency, and therefore can be sufficiently suppressed from migrating to the water phase when the oil phase is mixed.
[0028] The compound (a) is not particularly limited as long as it has an acyl group, an amino group and a -COOM group (M represents a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group), but is preferably the following formula (1).
[0029] R 1 -CONR 2 -R 3 -COOM(1)
[0030] (Where R 1 represents a hydrocarbon group having 1 to 30 carbon atoms, R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms. 3 represents a divalent hydrocarbon group having 1 to 20 carbon atoms which may optionally have a functional group. M represents a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group.
[0031] As the above R 1 The hydrocarbon group in is not particularly limited, and examples thereof include aliphatic alkyl groups having 1 to 30 carbon atoms, alicyclic alkyl groups having 3 to 30 carbon atoms, alkenyl groups having 2 to 30 carbon atoms, alkynyl groups having 2 to 30 carbon atoms, and aryl groups having 6 to 30 carbon atoms.
[0032] Examples of the alkyl group include methyl, ethyl, n-propyl, n-butyl, n-pentyl (amyl group, amyl group), n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, n-eicosyl, isopropyl, sec-butyl, isobutyl, tert-butyl, 1-methylbutyl, 1-ethylpropyl, 2-methylbutyl, isopentyl, neopentyl, 1,2-dimethylpropyl, 1,1-dimethylpropyl, tert-pentyl, 1,3-dimethylbutyl aliphatic alkyl groups such as cyclopropyl, cyclopropylmethyl, cyclobutyl, cyclobutylmethyl, cyclopentyl, cyclohexyl, cyclohexylmethyl, cycloheptyl, cyclooctyl, cyclohexylpropyl, cyclododecyl, norbornyl (C7), adamantyl (C10), and cyclopentylethyl.
[0033] Examples of the alkenyl group include vinyl, allyl, 1-butenyl, 2-butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, dodecenyl, octadecenyl, and eicosenyl.
[0034] Examples of the alkynyl group include ethynyl, 1-propynyl, 2-propynyl, butynyl, pentynyl, hexynyl, heptynyl, octynyl, nonynyl, decynyl, dodecynyl, octadecynyl and eicosynyl.
[0035] Examples of the aryl group having 6 to 30 carbon atoms include phenyl, naphthyl, benzyl, 1-phenylethyl, 2-phenylethyl, 3-phenylpropyl, 4-phenylbutyl, styryl (Ph-CH=C- group), cinnamyl (Ph-CH=CHCH2- group), 1-benzocyclobutenyl, 1,2,3,4-tetrahydronaphthyl and other aralkyl groups.
[0036] The above R 1 The hydrocarbon group in the carbon number is 1 to 30, preferably 3 to 28, more preferably 6 to 25, further preferably 8 to 22, and particularly preferably 10 to 18.
[0037] As the above R 1 The hydrocarbon group in is preferably an aliphatic alkyl group or an alkenyl group, and more preferably an aliphatic alkyl group.
[0038] The above R 2 It is a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms, and the hydrocarbon group is preferably an alkyl group having 1 to 5 carbon atoms.
[0039] As the above R 2 , preferably a hydrogen atom.
[0040] The above R 3 It is a divalent hydrocarbon group having 1 to 20 carbon atoms and optionally having a functional group. The divalent hydrocarbon group is preferably a group obtained by removing one hydrogen atom from an alkyl group, an alkenyl group, an alkynyl group or an aryl group. More preferably, it is a group obtained by removing one hydrogen atom from an alkyl group. Specific examples of the alkyl group are as described above.
[0041] The above R 3 The number of carbon atoms in the hydrocarbon group is preferably 1-15, more preferably 2-12, further preferably 2-10, and particularly preferably 2-8.
[0042] As the above R 3 The functional group optionally possessed is not particularly limited, and examples thereof include a carboxyl group or a salt thereof, an amino group, a hydroxyl group, a thiol group, an amide group, a guanidine group, an ester group, an ether group, etc. Among them, a carboxyl group or a salt thereof, an amino group, a hydroxyl group, a thiol group, an amide group is preferred, and a carboxyl group or a salt thereof is more preferred.
[0043] The above-mentioned M is a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group, preferably a hydrogen atom or an alkali metal.
[0044] Examples of the alkali metal include lithium, sodium, potassium, and the like, and sodium is preferred.
[0045] Examples of the organic ammonium salt that forms the organic ammonium group include methylammonium salt, ethylammonium salt, dimethylammonium salt, diethylammonium salt, trimethylammonium salt, and triethylammonium salt.
[0046] Examples of the organic amine forming the organic amine group include primary amines such as methylamine, ethylamine, propylamine, n-butylamine, sec-butylamine, tert-butylamine, cyclohexylamine, benzylamine and aniline; secondary amines such as dimethylamine, diethylamine, dipropylamine, dibutylamine, diisobutylamine, di-sec-butylamine, di-tert-butylamine, dicyclohexylamine, dibenzylamine and diphenylamine; tertiary amines such as trimethylamine, triethylamine, tripropylamine, tributylamine, tricyclohexylamine, tribenzylamine and triphenylamine; and alkanolamines such as ethanolamine, diethanolamine and triethanolamine.
[0047] As the above R 3 , preferably a group represented by the following formula (2).
[0048] -CH(R 4 )-(2)
[0049] (R 4 represents a hydrogen atom or a hydrocarbon group having 1 to 15 carbon atoms which may have a functional group.
[0050] As the above R 4 The hydrocarbon group in is preferably an alkyl group, an alkenyl group, an alkynyl group or an aryl group. More preferably, it is an alkyl group having 1 to 15 carbon atoms. Specific examples of the alkyl group are as described above.
[0051] The above R 3 The number of carbon atoms in the hydrocarbon group is preferably 1-12, more preferably 1-10, further preferably 1-8, particularly preferably 1-6.
[0052] As the above R 4 The optional functional group is not particularly limited, and specific examples and preferred embodiments are the same as those of R 3 The optional functional groups are the same.
[0053] The compound (a) is preferably an N-acylamino acid and / or a salt thereof.
[0054] The above-mentioned N-acylamino acid is a compound formed by condensation of a carboxylic acid and an amino group of an amino acid.
[0055] As the amino acid, at least one of the 20 amino acids forming proteins may be used, and specifically, alanine, arginine, asparagine, aspartic acid, cysteine, glutamine, glutamic acid, glycine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine, and valine may be mentioned. Among them, neutral amino acids and acidic amino acids are preferred, acidic amino acids are more preferred, and aspartic acid and glutamic acid are particularly preferred.
[0056] The carboxylic acid is not particularly limited, and examples thereof include saturated fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, neopentanoic acid, caproic acid, heptanoic acid, octanoic acid, 2-ethylhexanoic acid, nonanoic acid, decanoic acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, nonadecanoic acid, and arachidic acid; monounsaturated fatty acids such as acrylic acid, methacrylic acid, crotonic acid, myristoleic acid, palmitoleic acid, sapienic acid, oleic acid, trans-oleic acid, vaccenic acid, gadoleic acid, eicosenoic acid, erucic acid, and nervonic acid; diunsaturated fatty acids such as linoleic acid, eicosadienoic acid, and docosadienoic acid; α-linolenic acid, γ-linolenic acid, pinolenic acid, eleostearic acid, and mead acid; triunsaturated fatty acids such as linolenic acid, dihomo-gamma-linolenic acid, eicosatrienoic acid; tetraunsaturated fatty acids such as stearidonic acid, arachidonic acid, eicosatetraenoic acid, docosatetraenoic acid; pentaunsaturated fatty acids such as bosseopentaenoic acid, arachidonic acid, docosapentaenoic acid, osbond acid, carassius acid, tetracosapentaenoic acid; hexaunsaturated fatty acids such as docosahexaenoic acid, nisinic acid, etc.
[0057] Among them, saturated fatty acids, monounsaturated fatty acids, and diunsaturated fatty acids are preferred, and the above R 1 A carboxylic acid having a carboxyl group bonded to an alkyl or alkenyl group.
[0058] The salt of the N-acylamino acid is not particularly limited, and examples thereof include alkali metal salts such as sodium and potassium, and ammonium salts, among which sodium salts are preferred.
[0059] Specific examples of N-acylamino acids or salts thereof include lauroyl glutamic acid, myristoyl glutamic acid, palmitoyl glutamic acid, stearoyl glutamic acid, caproyl glutamic acid, capryloyl glutamic acid, oleoyl glutamic acid, linoleoyl glutamic acid, cocoyl glutamic acid, lauroyl aspartic acid, myristoyl aspartic acid, palmitoyl aspartic acid, stearoyl aspartic acid, caproyl aspartic acid, capryloyl aspartic acid, oleoyl aspartic acid, linoleoyl aspartic acid, cocoyl aspartic acid, and salts thereof. Among these, lauroyl glutamic acid, lauroyl aspartic acid, cocoyl glutamic acid, cocoyl aspartic acid, and salts thereof are preferred.
[0060] The coating amount of the compound (a) in the spherical calcium carbonate particles of the present invention is not particularly limited, and is preferably 1 to 10% by weight relative to 100% by weight of the coated spherical calcium carbonate particles, thereby enabling the effects of the present invention to be more fully exerted.
[0061] The coating amount of the compound (a) is more preferably 1 to 8% by mass, further preferably 2 to 7% by mass, and particularly preferably 3 to 6% by mass.
[0062] The coating amount can be calculated based on the carbon amount measured by a carbon analyzer and the molecular weight of the compound (a).
[0063] The shape of the calcium carbonate particles of the present invention may be spherical, and the sphericity defined by the ratio of the minor diameter to the major diameter is preferably 0.80 or more. Thus, when the calcium carbonate particles are made into cosmetics, the slipperiness on the skin and the color-blurring effect are further improved.
[0064] The particle size of the spherical calcium carbonate particles of the present invention is not particularly limited, and the median particle size (D50) measured by a laser diffraction / scattering particle size distribution measuring device is preferably 0.1 to 20 μm. Thus, the slip, adhesion and feel on the skin when the cosmetics are made are further improved.
[0065] The median particle size (D50) is more preferably 0.5 to 20 μm, further preferably 1 to 15 μm, and particularly preferably 3 to 10 μm.
[0066] The spherical calcium carbonate particles of the present invention preferably contain more than 90% of vaterite crystals, and more preferably contain 98 to 100% of vaterite crystals.
[0067] As is well known, the ratio of vaterite crystals in calcium carbonate can be calculated according to the following formula (3) (MS Rao, Bull. Chem. Soc. Japan, 46, 1414 (1973)).
[0068] The ratio of vaterite crystals F(v) = f(v) × 100 (3)
[0069] Here, f(v)=1-I 104(c) / (I 110(v) +I 112(v) +I 114(v) +I 104(c) ), I 104(c) is the X-ray diffraction intensity of the 104 face of calcite, I 110(v) is the X-ray diffraction intensity of the 110 face of vaterite, I 112(v) is the X-ray diffraction intensity of the 112 face of vaterite, I 114(v) is the X-ray diffraction intensity of the 114 face of vaterite.
[0070] The spherical calcium carbonate particles of the present invention have the property of not becoming too hard during solidification, and preferably have a needle puncture load of 1 to 15 mN as measured by the following method, and more preferably 1 to 10 mN.
[0071] (Method for measuring needle puncture load)
[0072] Spherical calcium carbonate particles were placed in a container until flattened, and a manual punch was used to apply a load of 6MPa for 20 seconds. After the load was released, a load of 6MPa was applied again for 20 seconds to make a molded body, and the load when a needle of 1mm in diameter was penetrated into 1mm was measured 3 times using a rheometer, and the average value was calculated.
[0073] The spherical calcium carbonate particles of the present invention are excellent in water repellency at high temperatures, and in the following water repellency evaluation test at 80° C., the proportion of the spherical calcium carbonate particles preferably in a state of floating on the water surface is more than 90%. In this way, even if the cosmetics formed by mixing are exposed to high temperatures, the emulsion system can also maintain stability.
[0074] (Water repellency evaluation at 80°C)
[0075] 1 g of spherical calcium carbonate particles was gently placed on the surface of 100 ml of pure water at 80° C., stirred at 60 rpm for 1 minute using a magnetic stirrer, and then the water repellency was evaluated.
[0076] The method for producing the spherical calcium carbonate particles of the present invention is not particularly limited, and preferably includes a step of mixing the raw calcium carbonate with the compound (a) (hereinafter also referred to as a mixing step).
[0077] The raw material calcium carbonate used in the mixing step may be any material as long as the obtained calcium carbonate particles are spherical, and the sphericity is preferably 0.80 or more.
[0078] In addition, the particle size of the raw material calcium carbonate is not particularly limited, but the median particle size (D50) measured by the above method is preferably 0.1 to 20 μm.
[0079] When the particle shape and particle size are as described above, powder particles having a good feel can be obtained.
[0080] In the above-mentioned mixing step, as long as the raw material calcium carbonate is mixed with the above-mentioned compound (a), there is no particular limitation, and preferably the raw material calcium carbonate and the compound (a) are added to a solvent and mixed. More preferably, calcium carbonate and / or compound (a) are dispersed or dissolved in a solvent and then mixed. Further preferably, compound (a) or a solution of compound (a) is added to a dispersion of calcium carbonate and mixed.
[0081] The solvent for dispersing or dissolving the calcium carbonate and / or compound (a) is not particularly limited, and examples thereof include: water; and water-soluble organic solvents, such as alcohols such as methanol, ethanol, n-propanol, isopropanol, polyols such as ethylene glycol, diethylene glycol, glycerol, pyrrolidone-based solvents such as N-methylpyrrolidone, ketone-based solvents such as acetone, etc. As the solvent, water is preferred.
[0082] In the method for producing the spherical calcium carbonate particles, one of the preferred embodiments is to add the compound (a) or an aqueous solution of the compound (a) to an aqueous dispersion of calcium carbonate and mix the mixture.
[0083] The amount of the compound (a) used in the mixing step is not particularly limited and can be adjusted to achieve a preferred coating amount, preferably 1 to 10% by weight relative to 100% by weight of the raw calcium carbonate, and more preferably 2 to 8% by weight.
[0084] In the mixing step, when the raw material calcium carbonate is prepared as a dispersion, the ratio of calcium carbonate in the dispersion is preferably 100 to 350 g, more preferably 150 to 300 g, relative to 1 L of the solvent.
[0085] The temperature in the mixing step is not particularly limited, but is preferably 10 to 100° C., more preferably 20 to 80° C., and even more preferably 25 to 40° C. This can more sufficiently reduce costs and change the shape of the calcium carbonate particles from spherical to cubic.
[0086] In the method for producing spherical calcium carbonate particles of the present invention, stirring is preferably performed after the above-mentioned mixing step.
[0087] The preferred temperature range in the stirring step is the same as the preferred temperature range in the mixing step.
[0088] The stirring time in the stirring step is not particularly limited, but is preferably 1 minute to 24 hours, more preferably 30 minutes to 18 hours, and even more preferably 1 hour to 10 hours.
[0089] The method for producing spherical calcium carbonate particles of the present invention preferably includes a washing step and a drying step after the mixing step (and the stirring step).
[0090] The above-mentioned cleaning process is not particularly limited, and the spherical calcium carbonate particles obtained through the mixing process (and the stirring process) are preferably filtered and washed. More preferably, the obtained spherical calcium carbonate particles are repeatedly filtered and washed until the conductivity of the filtrate reaches below 100 μS / cm. Thus, it is possible to more fully suppress the foaming etc. caused by the residual compound (a) etc. when preparing the spherical calcium carbonate particles.
[0091] The drying temperature in the drying step is preferably 50 to 150°C, more preferably 70 to 120°C, and even more preferably 80 to 110°C.
[0092] The drying time in the drying step is preferably 1 to 72 hours, more preferably 10 to 60 hours, and even more preferably 24 to 48 hours.
[0093] The spherical calcium carbonate particles of the present invention have excellent water repellency at high temperatures, and do not become too hard when solidified, and are easily spread on the skin, giving a dry touch, and therefore can be suitably used in cosmetics and the like.
[0094] A cosmetic comprising the spherical calcium carbonate particles of the present invention is also one of the present invention.
[0095] The cosmetics of the present invention include foundation, primer, emulsion, cream, eye shadow, blush, mascara, lipstick, sunscreen, etc. The cosmetics of the present invention can be made into any form of oily cosmetics, water-based cosmetics, O / W type cosmetics, and W / O type cosmetics. Among them, it can be particularly suitable for use in color cosmetics such as foundation, primer, eye shadow, basic cosmetics such as lotion, cream, emulsion, and beauty essence, and sunscreen.
[0096] In addition to the above-mentioned spherical calcium carbonate particles, any aqueous component and oily component that can be used in the cosmetics field can also be used in combination in the cosmetics of the present invention. As the above-mentioned aqueous component and oily component, it is not particularly limited, for example, it can contain oil content, surfactant, wetting agent, higher alcohol, metal ion screening agent, natural and synthetic polymer, water-soluble and oil-soluble polymer, ultraviolet shielding agent, various extracts, inorganic and organic pigments, various powders such as inorganic and organic clay minerals, inorganic and organic pigments, organic dyes, colorants, preservatives, antioxidants, pigments, thickeners, pH regulators, spices, cooling agents, antiperspirants, bactericides, skin activators and other ingredients. Specifically, for example, one or more of the compounding components listed in Japanese Patent Laid-Open No. 2014-080392 can be optionally mixed, and target cosmetics can be manufactured by conventional methods. The compounding amount of these compounding components is not particularly limited as long as it does not damage the scope of the effect of the present invention.
[0097] Example
[0098] The present invention is described in more detail below with reference to the following examples, but the present invention is not limited to these examples. It should be noted that, unless otherwise specified, "%" and "wt%" represent "weight % (mass %)". It should be noted that the determination methods of various physical properties are as follows.
[0099] (Median particle size D50)
[0100] The volume-based median diameter D50 was measured using a laser diffraction / scattering particle size distribution analyzer LA-750 manufactured by HORIBA, Ltd.
[0101] (Conductivity of filtrate)
[0102] The measurement was performed using a conductivity meter ES-12 manufactured by HORIBA, Ltd.
[0103] (Sphericity of spherical calcium carbonate particles)
[0104] 100 particles were randomly selected from the SEM images, their major and minor diameters were measured, and the minor / major diameter ratio was calculated.
[0105] (Water repellency evaluation at 25°C)
[0106] 1 g of each powder was gently placed on the surface of 100 ml of pure water at room temperature of 25° C., stirred at 60 rpm for 1 minute using a magnetic stirrer, and then the water repellency was visually judged according to the following criteria.
[0107] ○: Almost all of the powder was floating on the water surface.
[0108] △: More than half of the powder is in a state of floating on the water surface, but a part of the powder is in a state of being mixed with water.
[0109] ×: Most of the powder is in a state of being mixed with water.
[0110] (Water repellency evaluation at 80°C)
[0111] 1 g of each powder was gently placed on the surface of 100 ml of pure water at 80° C. and stirred at 60 rpm for 1 minute using a magnetic stirrer. The water repellency was then visually evaluated according to the following criteria.
[0112] ○: Almost all of the powder was floating on the water surface.
[0113] △: More than half of the powder is in a state of floating on the water surface, but a part of the powder is in a state of being mixed with water.
[0114] ×: Most of the powder is in a state of being mixed with water.
[0115] (Coating amount of compound (a))
[0116] Using a carbon analyzer EMIA-110 (manufactured by HORIBA, Ltd.), the amount of carbon detected at 500°C was divided by the weight ratio of all carbon in the molecule to the molecular weight of each surface treatment agent (compound (a)) (in Comparative Example 3, it is the weight ratio of all carbon to dimethylsiloxy units), and the calculated value was taken as the coating amount of compound (a).
[0117] (Evaluation of needle puncture load)
[0118] The powder was placed in a rectangular aluminum pan container until it was flattened, and a load of 6 MPa was applied for 20 seconds using a manual punch. After the load was released, a load of 6 MPa was applied again for 20 seconds to produce a molded body. For each molded body, a rheometer (CR-100 made by Sun Scientific Co., Ltd.) was used to measure the load when a needle with a diameter of 1 mm penetrated 1 mm three times, and the average value was calculated.
[0119] (Evaluation of viscosity when using thickener in combination)
[0120] Disperse 2 g of the powder in 5 g of 1,3-butanediol. Dilute 10 g of a 5 wt% aqueous solution of a thickener (ammonium acryloyldimethyltaurate / vinyl pyrrolidone) copolymer (Aristoflex AVC manufactured by Clariant AG) with 90 g of water, add the dispersion to it, and fully disperse it with a stirrer. Measure the viscosity after standing for 24 hours with a B-type viscometer. It should be noted that the viscosity is 11200 mPa·s when only the thickener is used.
[0121] <Example 1>
[0122] 100 g of spherical calcium carbonate (particle size 5 μm: KARUMARUSCS-M5 manufactured by Sakai Chemical Industry Co., Ltd.) was dispersed in 500 ml of water. Stirring was continued at 25°C for 30 minutes, and then a 25 wt% aqueous solution of sodium lauroyl aspartate (AminoFoamer manufactured by Asahi Kasei Finechem Co., Ltd.) was added. TM The mixture was stirred for 1 hour, filtered and washed with water (final conductivity: 92 μS / cm), and the obtained wet cake was dried overnight at 105° C. in a dryer to obtain powder 1.
[0123] <Example 2>
[0124] 100 g of spherical calcium carbonate (particle size 5 μm: KARUMARUS CS-M5 manufactured by Sakai Chemical Industry Co., Ltd.) was dispersed in 500 ml of water. Stirring was continued at 25° C. for 30 minutes, and then 4 g of sodium cocoyl glutamate (AMISOFT CS-11 manufactured by Ajinomoto Co., Inc.) was added. Stirring was continued for 1 hour, and then filtered and washed with water (final conductivity 95 μS / cm), and the obtained wet cake was dried overnight at 105° C. using a dryer to obtain powder 2.
[0125] <Example 3>
[0126] Powder 3 was obtained in the same manner as in Example 1 except that the amount of the 25 wt % sodium lauroyl aspartate aqueous solution was changed to 32 g. The final conductivity after water washing was 70 μS / cm.
[0127] <Example 4>
[0128] Powder 4 was obtained in the same manner as in Example 2 except that the amount of sodium cocoyl glutamate was changed to 2 g. The final conductivity after washing with water was 86 μS / cm.
[0129] <Example 5>
[0130] Powder 5 was obtained in the same manner as in Example 1 except that the amount of the 25 wt % sodium lauroyl aspartate aqueous solution was changed to 2 g. The final conductivity after water washing was 90 μS / cm.
[0131] <Comparative Example 1>
[0132] 100g of spherical calcium carbonate (particle size 5μm: KARUMARUSCS-M5 manufactured by Sakai Chemical Industry Co., Ltd.) was dispersed in 500ml of water. In addition, 5g of sodium stearate (manufactured by FUJIFILM Wako PureChemical Corporation) was dissolved in 858ml of warm water in another container. Next, the solution was added to the calcium carbonate dispersion at a rate of 50ml / min, and then heated to 70°C and stirred for 1 hour. It was then cooled to 25°C, neutralized to pH 7 using dilute hydrochloric acid, and stirred for 30 minutes. Filtered and washed with water (final conductivity 93μS / cm), the resulting wet cake was dried overnight at 105°C using a dryer to obtain powder 6.
[0133] <Comparative Example 2>
[0134] 100g of spherical calcium carbonate (particle size 5μm: KARUMARUSCS-M5 manufactured by Sakai Chemical Industry Co., Ltd.) was dispersed in 500ml of water. In addition, 5g of potassium myristic acid (manufactured by FUJIFILM Wako PureChemical Corporation) was dissolved in 858ml of warm water in another container. Next, the solution was added to the calcium carbonate dispersion at a rate of 50ml / min, and then heated to 70°C and stirred for 1 hour. It was then cooled to 25°C, neutralized to pH 7 using dilute hydrochloric acid, and stirred for 30 minutes. Filtered and washed with water (final conductivity 75μS / cm), the resulting wet cake was dried overnight at 105°C using a dryer to obtain powder 7.
[0135] <Comparative Example 3>
[0136] 100 g of spherical calcium carbonate (particle size 5 μm: KARUMARUS CS-M5 manufactured by Sakai Chemical Industry Co., Ltd.) and 50 ml of isopropyl alcohol in which 5 g of hydrogenated polydimethylsiloxane was dissolved were mixed and kneaded thoroughly for 1 hour and dried overnight at 105° C. in a dryer to obtain powder 8 .
[0137] <Comparative Example 4>
[0138] As powder 9, spherical calcium carbonate (particle size 5 μm: KARUMARU SCS-M5 manufactured by Sakai Chemical Industry Co., Ltd.) was used.
[0139] Table 1 shows the evaluation results of various physical properties of Examples 1 to 5 and Comparative Examples 1 to 4.
[0140] [Table 1]
[0141]
[0142] As can be seen from the evaluation results in Table 1, in Examples 1 to 5, the spherical calcium carbonate particles coated with the compound (a) have excellent water repellency even at high temperatures and a small needle load, so the effect of not becoming too hard can be obtained.
[0143] Also know that the spherical calcium carbonate particles of embodiment 1~4, when being used in combination with thickener, can maintain the viscosity equivalent to thickener when (11200mPa·s) and can not disturb thickener, when being used in combination with thickener in O / W emulsion etc., surface treatment of the present invention is also useful, can stably mix spherical calcium carbonate particles.
[0144] <Formulation Example 1>
[0145] An O / W emulsion foundation having the composition shown in Table 2 below was prepared.
[0146] [Table 2]
[0147] (Element) (wt%) 1. Stearic acid 0.7 2. Behenyl alcohol 0.5 3. Glyceryl Stearate 0.5 4. Squalane 8.0 5. Caprylic / capric triglyceride 4.0 6. Isotridecyl isononanoate 2.0 7. Sorbitan sesquioleate 0.5 8. (Acrylates / (C10-30) alkyl acrylate) cross-linked polymer (2% gel) 5.0 9. Polysorbate 80 1.2 10. (Ammonium acryloyldimethyltaurate / vinyl pyrrolidone) copolymer (5% gel) 10.0 11. Xanthan gum (2% gel) 2.0 12.1,3-Butanediol 7.0 13. Triethanolamine 0.75 14. Water 20.65 15. Powder 1 5.0 16. Titanium oxide dispersion (Note 1) 11.2 17. Iron oxide (yellow) dispersion (Note 2) 2.2 18. Iron oxide (red) dispersion (Note 3) 0.6 19. Iron oxide (black) dispersion (Note 4) 0.2 20. Water 18.0
[0148] (Note 1) DIP-T1 (N) (manufactured by Sakai Chemical Industry Co., Ltd.): titanium oxide 75 wt%, hydrogenated polydimethylsiloxane 1 wt%, 1,3-butylene glycol 22 wt%, PEG-9 polydimethylsiloxane 3 wt%
[0149] (Note 2) DIP-Y1 (N) (manufactured by Sakai Chemical Industry Co., Ltd.): 59 wt% yellow iron oxide, 1 wt% hydrogenated polydimethylsiloxane, 37.5 wt% 1,3-butylene glycol, 2.5 wt% PEG-9 polydimethylsiloxane
[0150] (Note 3) DIP-R1 (N) (manufactured by Sakai Chemical Industry Co., Ltd.): 49 wt% of red iron oxide, 1 wt% of hydrogenated polydimethylsiloxane, 48.5 wt% of 1,3-butylene glycol, 1.5 wt% of PEG-9 polydimethylsiloxane
[0151] (Note 4) DIP-K1 (N) (manufactured by Sakai Chemical Industry Co., Ltd.): 59 wt% black iron oxide, 1 wt% hydrogenated polydimethylsiloxane, 37.5 wt% 1,3-butylene glycol, 2.5 wt% PEG-9 polydimethylsiloxane
[0152] (Manufacturing method)
[0153] A: Mix ingredients 1 to 7 uniformly and heat to 80°C.
[0154] B: Mix components 8 to 14 uniformly and heat to 80°C.
[0155] C: Add A to B and emulsify.
[0156] D: Mix components 16 to 20 uniformly.
[0157] E: Add components 15 and D to C at 60°C or below and mix uniformly.
[0158] By blending powder 1, a 0 / W emulsion foundation excellent in both sedimentation resistance and touch can be obtained.
[0159] <Formulation Example 2>
[0160] A W / 0 cream having the composition shown in Table 3 below was prepared.
[0161] [Table 3]
[0162] (Element) (wt%) 1. Dimethyl polysiloxane 5.0 2. Methylphenyl polysiloxane 5.0 3. Squalane 8.0 4. Neopentyl glycol di(ethylhexanoate) 3.0 5. PEG-10 Dimethicone 3.0 6. Powder 2 5.0 7. Glycerin 10.0 8. Water 61.0
[0163] (Manufacturing method)
[0164] A: Components 1 to 5 are mixed and homogenized, and then 6 is added and uniformly mixed.
[0165] B: Mix ingredients 7 and 8 and stir.
[0166] C: Slowly add B to A while stirring.
[0167] By blending the powder 2, a W / O cream excellent in anti-settling property and touch can be obtained.
[0168] <Formulation Example 3>
[0169] A W / O sunscreen lotion having the composition shown in Table 4 below was prepared.
[0170] [Table 4]
[0171] (Element) (wt%) 1. Cyclopentasiloxane 15.0 2. Olefin oligomers 10.0 3. Dimethyl polysiloxane 2.0 4. PEG-9 polydimethylsiloxane 1.0 5. Neopentyl glycol di(ethylhexanoate) 5.0 6. Diisopropyl Sebacate 5.0 7.4-tert-Butyl-4′-methoxydibenzoylmethane 2.5 8. Trimethyl stearyl ammonium bentonite 0.2 9. Powder 1 5.0 10. Silicone treated zinc oxide (Note 5) 15.0 11. Water 35.3 12. Glycerin 3.0 13. Hydroxyethyl Cellulose 0.5 14. Phenoxyethanol 0.5
[0172] (Note 5) FINEX-52W-LP2 (manufactured by Sakai Chemical Industry Co., Ltd.): 86 wt% zinc oxide, 10 wt% silicon dioxide, 4 wt% hydrogenated polydimethylsiloxane
[0173] (Manufacturing method)
[0174] A: Mix components 1 to 5 evenly.
[0175] B: Components 6 to 7 are heated to 80°C, mixed and dissolved, and added to A.
[0176] C: Add ingredients 8-10 to B and mix vigorously to fully disperse.
[0177] D: Components 11 to 14 are heated to 95°C and mixed to dissolve, and then slowly mixed into C while stirring.
[0178] E: Mix thoroughly and evenly, then cool to 25°C to obtain a sunscreen lotion.
[0179] By using Powder 1, a W / O sunscreen emulsion excellent in both sedimentation resistance and touch was obtained.
[0180] <Formulation Example 4>
[0181] A powder foundation having the composition shown in Table 5 below was prepared.
[0182] [Table 5]
[0183]
[0184] (Note 6) HG-LFP (manufactured by Sakai Chemical Industry Co., Ltd.): 98.9 wt% barium sulfate, 1.0 wt% palmitic acid, 0.1 wt% magnesium hydroxide
[0185] (Note 7) FINEX-50S-LP2 (manufactured by Sakai Chemical Industry Co., Ltd.): 96 wt% zinc oxide, 4 wt% hydrogenated polydimethylsiloxane
[0186] (Note 8) MKR-1S (manufactured by Sakai Chemical Industry Co., Ltd.): 98.5 wt% titanium oxide, 1.5 wt% hydrogenated polydimethylsiloxane
[0187] (Note 9) Y-2300X (manufactured by YAMAGUCHI MICA CO., LTD): mica 98 wt%, hydrogenated polydimethylsiloxane 2 wt%
[0188] (Note 10) PDM-5L (S) (manufactured by TOPY INDUSTRIES CO., LTD): 98 wt% phlogopite, 2 wt% hydrogenated polydimethylsiloxane
[0189] (Note 11) SA-TARUKU JA-46R (manufactured by Miyoshi Kasei Co., Ltd.): 98 wt% talc, 2 wt% hydrogenated polydimethylsiloxane
[0190] (Note 12) SI-Red R-516PS LHC (manufactured by Miyoshi Kasei Co., Ltd.): 98 wt% red iron oxide, 2 wt% hydrogenated polydimethylsiloxane
[0191] (Note 13) SI-YelloW LL-100P LHC (manufactured by Miyoshi Kasei Co., Ltd.): 98 wt% yellow iron oxide, 2 wt% hydrogenated polydimethylsiloxane
[0192] (Note 14) SI-Black BL-100P LHC (manufactured by Miyoshi Kasei Co., Ltd.): black iron oxide 98 wt%, hydrogenated polydimethylsiloxane 2 wt%
[0193] (Manufacturing method)
[0194] A: Mix components 1 to 14 using a mixer.
[0195] B: Use a press to compact.
[0196] By using the powder 1, a powder foundation which is not rough and has a good touch can be obtained.
[0197] <Formulation Example 5>
[0198] A powder foundation having the composition shown in Table 6 below was prepared.
[0199] [Table 6]
[0200] (Element) (wt%) 1. Powder 2 10.0 2. Silicone treated mica (note 9 above) 30.8 3. Silicone treated talc (note 11 above) 15.0 4. Silicone treated titanium oxide (note 8 above) 10.0 5. Silicone treated synthetic phlogopite (note 10 above) 10.0 6. Silicone treated red iron oxide (note 12 above) 0.5 7. Silicone treated yellow iron oxide (note 13 above) 2.0 8. Silicone treated black iron oxide (note 14 above) 0.2 9. Polymethyl methacrylate 10.0 10. Polydimethylsiloxane (500cst) 5.0 11. Isononyl Isononanoate 3.0 12. Squalane 2.0 13. Vaseline 1.0 14. Phenoxyethanol 0.5
[0201] (Manufacturing method)
[0202] A: Mix components 1 to 14 using a mixer.
[0203] B: Set the weight of A to 100, add 50 parts of light liquid isoparaffin, and mix evenly with a mixer.
[0204] C: Fill the slurry of B into a pan and perform compression molding while applying vacuum.
[0205] D: The molded product of C was dried at 70°C for 10 hours to obtain a powder foundation.
[0206] By using the powder 2, a powder foundation having a good touch can be obtained.
Claims
1. A spherical calcium carbonate particle coated with a compound (a), wherein the compound (a) has an acyl group, an amino group and a -COOM group, and M represents a hydrogen atom, an alkali metal, an ammonium group, an organic ammonium group or an organic amine group.
2. The spherical calcium carbonate particles according to claim 1, wherein The compound (a) is an N-acylamino acid and / or a salt thereof.
3. The spherical calcium carbonate particle according to claim 1 or 2, wherein The median particle size (D50) of the spherical calcium carbonate particles measured by a laser diffraction / scattering particle size distribution measuring device is 0.1 to 20 μm.
4. The spherical calcium carbonate particles according to claim 1 or 2, wherein The coating amount of the compound (a) is 1 to 10% by weight relative to 100% by weight of the coated spherical calcium carbonate particles.
5. A cosmetic comprising the spherical calcium carbonate particles according to claim 1 or 2.
Citation Information
Patent Citations
Method for producing surface-treated spherical calcium carbonate particle for cosmetic
JP2012240930A
Coloration resin coated metallic sheet
JP2014061689A
Production method of titanium oxide particle for cosmetic
JP2014080392A